Brown rice authenticity evaluation by spark discharge-laser-induced breakdown spectroscopy - Pérez Rodríguez, Michael (2019)
Fil: Pérez Rodríguez, Michael. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas Naturales y Agrimensura; Argentina.